2019
DOI: 10.1370/afm.2407
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of External Practice Support to Improve Cardiovascular Risk Factors in Primary Care

Abstract: PURPOSE We conducted a randomized controlled trial to compare the effectiveness of adding various forms of enhanced external support to practice facilitation on primary care practices' clinical quality measure (CQM) performance. METHODS Primary care practices across Washington, Oregon, and Idaho were eligible if they had fewer than 10 full-time clinicians. Practices were randomized to practice facilitation only, practice facilitation and shared learning, practice facilitation and educational outreach visits, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Additionally, the exposure indicators suggest that professionals assigned to execute the strategy through sequential engagement of colleagues (starting with nurses who later sought the engagement of the physicians) had an unexpectedly higher degree of exposure to the implementation strategy actions, particularly in the case of nurses, the staff responsible for providing the active element of the clinical intervention. As described in the literature, commonly reported obstacles faced by physicians to fully engaging in implementation actions included heavy workload, staff turnover, di culties in investing time and effort improvement initiatives beyond providing care, and existing practice priorities [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the exposure indicators suggest that professionals assigned to execute the strategy through sequential engagement of colleagues (starting with nurses who later sought the engagement of the physicians) had an unexpectedly higher degree of exposure to the implementation strategy actions, particularly in the case of nurses, the staff responsible for providing the active element of the clinical intervention. As described in the literature, commonly reported obstacles faced by physicians to fully engaging in implementation actions included heavy workload, staff turnover, di culties in investing time and effort improvement initiatives beyond providing care, and existing practice priorities [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…We designed the project based on our experiences working with over 100 primary care practices on quality improvement activities for cardiovascular health, including tobacco cessation. 22 ORPRN's goals for the tobacco project included increasing the capacity of rural primary care practices to routinely screen for, document, and counsel patients about tobacco use. After conducting a needs assessment, ORPRN created a project that began with a 5-session ECHO program for clinical and CCO quality improvement staff.…”
Section: Reducing Tobacco Prevalencementioning
confidence: 99%
“…Healthy Hearts Northwest (H2N) took place within 209 smaller (10 or fewer clinicians) primary care practices across Washington State, Oregon and Idaho and the results of this randomized trial have been previously reported. 26 All practices were supported by a practice facilitator (PF) for 15 months.…”
Section: Study Setting and Subjectsmentioning
confidence: 99%